The impact of customer boredom on the efficacy of a rewards program - Axel Stock; Minoo Talebi Ashoori (Journal of Economy and Technology)
In this paper, we study utilizing a game theoretic model, how variety seeking triggered by customer boredom may affect a firm’s rewards program, pricing strategy and profits. Customer Boredom is conceptualized as a utility loss resulting from the purchase of a previously consumed brand. We analyze a two period model where two firms compete for a market of forward looking consumers by selling horizontally differentiated brands. When making the purchase decision in the second period, consumers trade off the utility loss from boredom with the benefits from obtaining the reward offered. In our analysis, we interestingly find that depending on consumers’ discount factor, firm profits either strictly increase or follow a u-shaped relationship with customer boredom. We also consider the case when brands differ in quality and show that under some conditions the high-quality firm’s profits decline while the low quality firm benefits when variety seeking due to boredom increases.